Microbiological quality assessment of Chapila (Gudusia chapra) and Tengra (Mystus vittatus) in Bangladesh - Quaiyum, Md Abdul; Rahman, Md Mofizur; Sarker, Bhakta Supratim; Alam, Md Masud; Khan, Najmus Sakib; Rahman, Mohammad Shamsur; Siddiqui, Rokeya (Stamford Journal of Microbiology, 2013)
Present study was conducted to determine and quantify the occurrence of various types of microorganisms in raw and final products of Chapila (Gudusia chapra) and Tengra (Mystus vittatus) and also to enhance food safety with a view of promoting international trade. Raw and frozen Chapila and Tengra samleswere collected and the microbial analysis was conducted. In case of raw product of Chapila, the aerobic plate count (APC) was 2.6×105 cfu/g, whereas in frozen products, the load was estimated to be 4.0×105 cfu/g. Furthermore, while APC of raw Tengra was 2×105 cfu/g, the APCs were 3.3×106 cfu/g in frozen product. Total coliform in raw and frozen Chapila was found to be 36.00 ± 2.3 MPN/g and 7.2 ± 1.01 MPN/g, respectively and 27.00 ± 5.57 MPN/g and 9.4 ± 3.75 MPN/g, respectively were found in raw and frozen Tengra samples. Moreover, Fecal coliform in frozen samples of Chapila and Tengra was found within the acceptable limit (<3 MPN/g). Salmonella spp. and Vibrio cholerae were not detected in any of the raw and frozen Chapila and Tengra samples. Overall, the present study reveals that tested frozen fish samples from the fish processing plant were good enough for export and of better quality than raw fish samples from the microbiological point of view. DOI: http://dx.doi.org/10.3329/sjm.v2i1.15203 Stamford Journal of Microbiology, Vol.2(1) 2012: 6-9